STRATEGI PENGEMBANGAN USAHA MIKRO MILIK MAHASISWA - Rosyadi, Imron (Universitas Muhammadiyah Surakarta, 2013)
The purpose of this research isÂ arrange a strategy model for developing micro and small enterprises owned by the student on the Colleges strategic role-based. Research conducted in the selected region: Surakarta, Sukoharjo, Klaten and Boyolali Regency. The data used is primary andÂ secondary data. PrimaryÂ dataÂ isÂ obtainedÂ usingÂ theÂ techniques of observation,Â focus group discussion (FGD) and in-depth interview on micro and small entrepreneurâs students in the area of Â research, the secondary data is obtainedÂ from various publication sources. Analytical method used is descriptive-analytic approach. This resultÂ showedÂ that: (1) micro and small enterprises owned byÂ student face various problems especially capital aspect, enterprisesÂ management andÂ entrepreneurship skills; (2) the problems that have been identified is used a basis of arrangement a SWOT analysis from formulating a grand strategy and model development of micro and small enterprises (FigureÂ 4.3);Â (3) TheÂ strategicÂ roleÂ ofÂ theÂ CollegesÂ inÂ developingÂ microÂ andÂ small enterprise:Â (a)Â formulatingÂ strategic for the developingÂ ofÂ small and micro enterprises through: (i) the teaching of entrepreneurship and enterprises management soft skills-based and (ii) conducting education and training an intensive, systematic and integrated about enterprises management and entrepreneurship science and technology-based; (b) colleges synergizeÂ withÂ BanksÂ andÂ HPMIÂ forÂ purposesÂ relatedÂ toÂ theÂ evaluationÂ ofÂ the feasibility businessÂ plan,Â flankingÂ businessÂ andÂ businessÂ consultant for entrepreneurs students; (c) providingÂ easeÂ ofÂ access to capital forÂ entrepreneursÂ students his business plan is considered feasible by a team of assessment.